Pengembangan Panduan Praktikum IPA Berbantuan Laboratorium Virtual Phet pada Sub Materi Asam Basa Untuk Siswa Kelas VII SMP/MTs - Susanti, Laily Yunita; Norma Kholilah (Edukimbiosis: Jurnal Pendidikan IPA, 2023)
Theory of Natural science in junior high school is considered difficult by learners; one of them is the sub material of acid base. It needs to be held practicum based learning. Meanwhile, for carrying out practicum, the tools and materials did not function properly. Besides that, there were no practical instructions in the schools. The purpose of this research (1) To find out the validity of the natural science practicum guide (2) to find out the student’s responses to the natural science practicum guide. The type of research used was R and D which is ADDIE model. The results of the media development were natural science practicum guide assisted by the Phet virtual laboratory, the validation results from material experts 97,5%, the validation result from media expert 94% and practitioner validation results 95,4% with a very valid category from each validator assessment, The student response test results on small scale were 89,3% and the large scale were 91,5% with a very interesting category.